Maternal Gut Microbiota Composition and Inflammatory Cytokines Before and After Delivery. (July 2016) - Hermansson, Henriina; Rautava, Samuli; Isolauri, Erika
Abstract : Introduction: The metabolic and immunologic changes during pregnancy endorse the growth and development of the foetus (1). The composition of the gut microbiota changes in parallel (2) but little is known about the significance of the gut microbiota in pregnancy and the pace of recovery after delivery. Methods: A nested case-control study based on a prospective intervention trial (3) was conducted. Altogether 10 women who had delivered by elective caesarean section (CS) and 13 women with non-elective CS were selected for this study. Women who had delivered vaginally (n = 23) were chosen as controls and matched for pre-pregnancy BMI, probiotic intervention during pregnancy as well as antibiotic exposure during pregnancy and labour. Blood and faecal samples were collected at the third trimester of pregnancy and one month postpartum. The composition of the gut microbiota was assessed by qPCR. The concentrations of the cytokines IL-1, IL-6, IL-8, IL-10, MCP-1, TNF-α were measured from serum. Results: One month after delivery the gut microbiota composition had not changed from the situation at the third trimester. Against this trend, faecal Clostridium coccoides numbers were higher in mothers after vaginal delivery as compared to those who had delivered by CS (p = 0.0001). The serum concentrations pro-inflammatory cytokines were higher one month postpartum than in the third trimester of pregnancy (Table 1). Discussion: Pregnancy alters the gut microbiota composition (1) and these pro-inflammatory changes seen at the third trimester of pregnancy have not yet normalized one month after delivery. A parallel pro-inflammatory tone was manifested in the serum cytokine profile indicating that the inflammatory state continues after pregnancy. The mode of delivery plays little role in these phenomena. Therefore probiotic intervention in attempt to reduce the risk of inflammatory conditions may need extension beyond the perinatal period.